Rice straw degradation by Pseudomonas aeruginosa AMB-CD-1, isolated from fresh cow dung and its impact on rice plants - Kishan Raj; Anup Singh; Tapas Chowdhury; S Gupta; Ravindra Soni (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Rice straw degradation in the soil is slow because of the high percentage of complex carbohydrates. Hence, farmers prefer to burn it in the agricultural field as a quicker alternative to the open burning of rice straw. Therefore, this study aims to characterize the bacteria from cow dung that can degrade rice straw.Method In the present study, four bacterial isolates were isolated from the fresh cow-dung sample. After initial screening, one isolate, i.e. AMB-CD-1, was used to degrade rice straw for 25 days. The degraded straw samples were then analyzed through FTIR and SEM analysis. Furthermore, the degraded sample was used for growing paddy plants.Results Out of four isolates, only the AMB-CD-1 isolate performed the best in all the screening analyses. The results concluded that the AMB-CD-1 culture inoculated straw had a low level of cellulose and hemicellulose, indicating these particles’ degradation. The isolated AMB-CD-1 was identified as Pseudomonas aeruginosa through the Sanger sequencing technique of the 16S rRNA gene. Results also revealed that the highest germination percentage, shoot weight and shoot length were found to be significantly superior in T4 (50% Sand + 50% Compost) whereas the highest chlorophyll content was found in T7 (25% Sand + 25% Soil + 50% Compost), and T1 (100% Sand) was effective in terms of root length.Conclusion Overall, the study concluded that Pseudomonas aeruginosa AMB-CD-1 might be a fast decomposer of paddy straw.